The Influence of Quality Perception, Price Fairness, Brand Experience, and Accessibility to Repurchase Interest (Study on Consumer Chatime in Purwokerto) - Hakim, Naufal; Suwandari, Lusi; Nawarini, Alisa Tri (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
The purpose of this study is to identify and analyze the effect of perceived quality, price fairness, brand experience, and accessibility towards repurchase intention. The sample in this study is 107 respondents who are the customer of Chatime Purwokerto. The determination of the sample used purposive sampling method. The data was analyze using multiple regression analysis. The result of this study indicates that perceived quality, price fairness, and brand experience affects on repurchase intention partially. While, price fairness have no affect on repurchase intention. The adjusted coefficient of determination R Square is 0,407, which means that perceived quality, price fairness, brand experience, and accessibility are affects on repurchase intention by 44,7%, while remaining 59,3% is affected by other variables that not examined in this study. The most dominant influence variable in this study is brand experience.